Exosomes derived from MSC as drug system in osteoarthritis therapy - Wen, Shuzhan; Huang, Xin; Ma, Jingchun; Zhao, Guanglei; Ma, Tiancong; Chen, Kangming; Huang, Gangyong; Chen, Jie; Shi, Jingsheng; Wang, Siqun (Frontiers in Bioengineering and Biotechnology, 2024)
Osteoarthritis (OA) is the most common degenerative disease of the joint with irreversible cartilage damage as the main pathological feature. With the development of regenerative medicine, mesenchymal stem cells (MSCs) have been found to have strong therapeutic potential. However, intraarticular MSCs injection therapy is limited by economic costs and ethics. Exosomes derived from MSC (MSC-Exos), as the important intercellular communication mode of MSCs, contain nucleic acid, proteins, lipids, microRNAs, and other biologically active substances. With excellent editability and specificity, MSC-Exos function as a targeted delivery system for OA treatment, modulating immunity, inhibiting apoptosis, and promoting regeneration. This article reviews the mechanism of action of MSC-Exos in the treatment of osteoarthritis, the current research status of the preparation of MSC-Exos and its application of drug delivery in OA therapy.